Factors Related to The Role Of Caregiver for Children with Epilepsy in Panti Syap Kasih - Martinus Geneo; Filia V. Tiwatu; Gladis Ratuliu (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Epilepsy is a chronic brain disease characterized by spontaneous, recurrent seizures and no improvement in each seizure. One measure of epilepsy therapy is the reduction or disappearance of seizures. One of the things that still causes uncontrolled seizures is compliance The measurement of patients and parents/caregivers’ adherence is one of the tools to find out the therapy and intervention needed. The role of caregiver for pediatric patients with epilepsy in improving health services is still not optimal. The care of children with epilepsy at Panti Sayap Kasih is an experience-based effort provided by a caregiver for children with epilepsy with the aim of controlling the incidence of epilepsy in children. The purpose of this study was to find out the factors that could be related to the role of the caregiver for children with epilepsy in improving health services at the Panti Wing Kasih. This research is quantitative research using cross sectional study design, in which the researchers want to know the relationship of the independent variables and the dependent variable. This study was conducted on children with epilepsy at the Panti Sayap Kasih Woloan Tomohon-North Sulawesi. The sampling method used was the total sampling method, as many as 22 caregivers at the Panti Sayap Kasih.